2019
DOI: 10.1177/1369433219868932
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table test on seismic performances of newly designed joints for mountain tunnels crossing faults

Abstract: The zones where tunnels pass through faults are considered to be severely damaged during earthquakes. Site investigation of tunnels crossing faults revealed that there were different types of damage patterns after earthquakes. This article proposed a new seismic design concept of “guiding” and “yielding.” Two types of joints, multilevel brittle-flexible joint and flexible joint, were based on this concept and were investigated in this study. A series of shaking table tests were conducted on reduced scale tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Substituting (10) into (6), the expansion direction can be determined by (8) and (9). In particular, when the material is isotropic and other affecting factors are not taken into account, σ ic � σ 0 , τ θc � τ 0 , E i � E 0 , and G θ � G 0 are all constants, and then (6) can be simplified to…”
Section: Sedr Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Substituting (10) into (6), the expansion direction can be determined by (8) and (9). In particular, when the material is isotropic and other affecting factors are not taken into account, σ ic � σ 0 , τ θc � τ 0 , E i � E 0 , and G θ � G 0 are all constants, and then (6) can be simplified to…”
Section: Sedr Principlementioning
confidence: 99%
“…e second aspect is the experimental researches on tunnel models. For instance, large shaking table model tests [5][6][7][8][9] were conducted, which have obtained fruitful achievements in the field of seismic affecting factors of lining structures. e third aspect is seeking breakthroughs in theoretical analyses, which focuses on establishing constitutive models to obtain the stress state of lining structures with seismic excitation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Lining. e mechanical parameters of composite lining were obtained from practical engineering [44]. After a series of material tests, water, plaster, diatomite, quartz sand, and barite were adopted to simulate the composite lining with the ratio of 1 : 0.6 : 0.2 : 0.1 : 0.4 [45].…”
Section: E Similar Materials Of Tunnelmentioning
confidence: 99%
“…A mixture of fly ash, river, sand, and machine oil was selected to simulate the similar materials of surrounding rocks [44][45][46]. e ratio of hard rock was fly ash:river sand:oil � 50 : 40 : 10, and the ratio of soft rock was fly ash:river sand:oil � 45 : 40 : 15.…”
Section: Similar Materials Of Surrounding Rockmentioning
confidence: 99%
“…A large number of tunnel projects in China that are under construction or have already been built, are located in earthquake-prone areas, especially in the southwest. The seismic response of tunnels in areas of high earthquake intensity is a problem that must be faced in current tunnel construction, especially for tunnels through fault fracture zones [1][2][3]. The "5.12" Wenchuan earthquake indicated that tunnels with good engineering geological conditions show good seismic performance, while tunnels with complex geological conditions, including major changes of strata or poor rock properties, are more vulnerable to seismic damage.…”
Section: Introductionmentioning
confidence: 99%